Bacteriological study of Payra river: microbial isolation, identification, analysis of antimicrobial resistance and pathogenicity - Rahman, Ismam Nashid; Shudha, Farzana Yeasmin; Ebnat, Kazi Anika; Fatima, Nayara Noor-E (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.